Synthesis of cyclodextrin (CD) using immobilized enzyme on hollow - Suhaily, Suhaimi (2019)
Cyclodextrin (CD) is produced by the enzymatic reaction of cyclodextrin glucanotransferase (CGTase) in the present of starch as a substrate. The CD has the ability to act as encapsulating agent and also additives in many applications. However, the used of CGTase is often limited due to the instability of the enzyme and easily denatured during the production of CD. Hence, enzyme immobilization has been widely explored to overcome these problems. Various immobilization methods and supports have been investigated over the years, yet less study was conducted in detail on the effect of reaction parameters for the production of CD by using immobilized CGTase. The objectives of this study were to determine and to optimize the effect of reaction parameters for the production of CD by using the immobilized CGTase on polyvinylidene difluoride (PVDF) hollow fiber membrane. The effect of starch type, starch concentration, temperature, pH, reaction time and agitation rate on the CD production were determined by using one factor at a time (OFAT). The results revealed that 3% (w/v) of soluble potato starch produced the highest amount of CD (5.22 mg/mL). The production of CD was also the highest at temperature of 40°C (5.21 mg/mL), pH 6 (4.62 mg/mL), 6 h of reaction time (4.37 mg/mL) and 150 rpm of agitation rate (4.38 mg/ml). From the result, immobilized CGTase managed to produce 2 to 3-fold higher of CD production than the free CGTase. The screening of the significant reaction parameters for the production of CD were conducted by using fractional factorial design (FFD). The results showed that the concentration of soluble potato starch concentration, pH and temperature were the most significant parameters on the production of CD. The reaction parameters were then optimized by using central composite design (CCD). Under the optimized conditions (3.2% w/v concentration of soluble potato starch, 45.2°C of reaction temperature and pH 5.6), the production of CD was 3.2-fold higher than the amount of CD before the optimization process. The immobilized enzyme was successfully retained up to 38% of the initial activity and can be reused for 10 cycles for the production of CD. Therefore, the immobilization of CGTase on hollow fiber membrane proved to be suitable to enhance the production of CD with high enzyme stability.